INTEGRATING YOGA INTO SPORTS PHYSIOLOGY: EFFECTS ON HEART RATE VARIABILITY AND AUTONOMIC FUNCTION TESTING FOR ATHLETIC PERFORMANCE ENHANCEMENT - Dr Manu saini; Dr Prem chand lamba; Dr Divya Joshi; Dr Himanshu Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Heart Rate Variability (HRV) and autonomic function are essential physiological markers determining athletic performance and recovery. What remains underexplored are autonomic adaptations associated with traditional endurance training attempts that emphasize adaptations in cardiovascular and muscular systems. Several hypotheses have been proposed for which yoga, which integrates Pranayama (breath control), Asanas (postures), and Dhyana (meditation) has been hypothesized to promote autonomic and performance enhancement. This study investigates the impact of a 12-week yoga intervention on HRV, autonomic function, and endurance performance in athletes. Methods: A quasi-experimental study was done of 40 endurance athletes of Jaipur (n=20 experimental and n=20 control receiving conventional training) and the experimental received the yoga training. At baseline, 6 weeks, and 12 weeks, HRV parameters (RMSSD, SDNN, LF/HF ratio), autonomic function tests (Deep Breathing Test, Valsalva Ratio, Orthostatic HR Change,) and performance metrics (VO₂ max, heart rate recovery, 1.5 km run time) were assessed. SPSS 27.0 was used for statistical analysis and repeated measures ANOVA and paired t-tests were conducted. Results: Significant improvements (45.2 ms vs. 63.4 ms, 58.3 ms vs. 72.9 ms, and 2.1 vs. 1.3) in RMSSD, SDNN, and LF/HF ratio, respectively, confirm higher autonomic stability in the experimental group. Valsalva Ratio improved from 1.5 to 2.0 and VO₂ max increased from 48.2 to 55.8 ml/kg/min. All parameters remained unchanged in the control group. Conclusion: Levels of autonomic regulation, cardiovascular efficiency,y as well as endurance performance,e significantly increase with yoga. Yoga can be an important addition to endurance athletes’ training regimens to optimize recovery, prevent overreaching and overtraining, and increase physiological resilience.